Consuming Finnishness: Immigrants’ engagement with local brands, acculturation and identity negotiation in Finland - Sambacka, Iana (My University, 2026)
Adjustment to a new society is not a simple process, as it requires the reconsideration of many everyday practices. One such practice is consumption. In the host society, local brands may function as cultural symbols that reflect the society’s values, practices, and shared meanings. The objective of this study is to examine how immigrants living in Finland engage with and relate to Finnish local brands through consumption, and how these consumption practices connect to identity negotiation. The study focuses on Finnishness as the cultural context in which local brands are consumed. The theoretical discussion draws on consumer acculturation, cultural meaning, brand consumption, the cultural meanings of brands, and identity negotiation. At the end of the theoretical section, a conceptual framework is presented to structure the central levels of the study. At the first level, acculturation functions as the broader context in which individual actions and experiences are situated. At the second level, identity negotiation in the host society is examined. At the third level, the focus is on the consumption of Finnish local brands as an everyday practice, including both practical engagement with brands and the meanings attached to them. In this framework, Finnishness is understood as the cultural and symbolic environment through which local brand consumption becomes meaningful. The study was conducted within a qualitative, interpretivist research paradigm. The empirical material consists of ten semi-structured interviews. The data were analysed using thematic analysis, with attention to recurring themes, differences between participants, and contextual meanings. The findings show that Finnishness was understood not only as national identity, but also as a recognisable cultural style associated with calmness, order, personal space, honesty, nature, restraint, and practicality. In participants’ everyday lives, Finnish local brands became visible especially through routine consumption, trust, familiarity, perceived quality, and social recognition. For some participants, consuming Finnish brands supported a sense of belonging and helped them feel socially accepted in Finnish society.At the same time, the findings show that Finnish brand consumption was not always conscious, symbolic, or guided by identity-related concerns. In many cases, Finnish brands gradually became a natural part of everyday life. Overall, the study suggests that Finnish local brands can function as cultural resources in immigrants’ identity negotiation and sense of belonging, but their role is context-dependent and often subtle. Local brands do not operate as direct indicators of integration. Instead, their meaning is constructed through everyday practices, social recognition, and broader cultural meanings related to Finnishness.

Sopeutuminen uuteen yhteiskuntaan ei ole yksinkertainen prosessi, sillä se edellyttää monien arkipäiväisten käytäntöjen uudelleentarkastelua. Yksi tällainen käytäntö on kuluttaminen. Vastaanottavassa yhteiskunnassa paikalliset brändit voivat toimia kulttuurisina symboleina, jotka heijastavat yhteiskunnan arvoja, käytäntöjä ja jaettuja merkityksiä. Tämän tutkimuksen tavoitteena on tarkastella, miten Suomessa asuvat maahanmuuttajat suhtautuvat suomalaisiin paikallisiin brändeihin kulutuksen kautta ja miten nämä kulutuskäytännöt kytkeytyvät yksilön identiteetin muodostumiseen. Tutkimus keskittyy suomalaisuuteen erityisenä kulttuurisena kontekstina, jossa paikallisia brändejä kulutetaan. Teoreettinen tarkastelu rakentuu kuluttaja- akkulturaation, kulttuurisen merkityksen muodostumisen, brändikulutuksen, brändien kulttuuristen merkitysten sekä identiteetin ja kuulumisen käsitteiden varaan. Teoreettisen osuuden lopussa esitetään käsitteellinen viitekehys, joka jäsentää tutkimuksen keskeiset tasot. Ensimmäisellä tasolla akkulturaatio toimii laajempana kontekstina, johon yksilön toiminta ja kokemukset sijoittuvat. Toisella tasolla tarkastellaan identiteetin muodostumista vastaanottavassa yhteiskunnassa. Kolmannella tasolla tarkastelun kohteena on suomalaisten paikallisten brändien kulutus konkreettisena arjen toimintana. Tällä tasolla korostuvat sekä brändien käytännöllinen käyttö että niihin liittyvien merkitysten muodostuminen. Suomalaisuus ymmärretään tässä viitekehyksessä kulttuurisena ja symbolisena ympäristönä, jossa paikallisten brändien kulutus saa merkityksensä. Tutkimus on toteutettu laadullisessa ja interpretatiivisessa tutkimusparadigmassa. Empiirinen aineisto koostuu kymmenestä puolistrukturoidusta haastattelusta. Aineisto analysoitiin temaattisen analyysin avulla kiinnittäen huomiota toistuviin teemoihin, osallistujien välisiin eroihin sekä kontekstuaalisiin merkityksiin. Tulokset osoittavat, että suomalaisuus ymmärrettiin paitsi kansallisena identiteettinä myös tunnistettavana kulttuurisena tyylinä, johon liitettiin rauhallisuus, järjestys, henkilökohtainen tila, rehellisyys, luonto, pidättyväisyys ja käytännöllisyys. Osallistujien arjessa suomalaiset paikalliset brändit tulivat näkyviksi erityisesti rutiininomaisen kulutuksen, luottamuksen, tuttuuden, koetun laadun ja sosiaalisen tunnistettavuuden kautta. Osalle osallistujista suomalaisten brändien kuluttaminen tuki kuulumisen tunnetta ja auttoi heitä kokemaan itsensä sosiaalisesti hyväksytyiksi osaksi suomalaista yhteiskuntaa. Samanaikaisesti tulokset osoittavat, että suomalaisten brändien kulutus ei ollut aina tietoista, symbolista tai identiteettikysymysten ohjaamaa. Monissa tapauksissa suomalaiset brändit muuttuivat ajan myötä luonnolliseksi osaksi arkipäiväistä elämää. Tutkimus osoittaa, että suomalaiset paikalliset brändit voivat toimia kulttuurisina resursseina maahanmuuttajien identiteetin muodostumisessa ja kuulumisen kokemuksessa, mutta niiden rooli on kontekstisidonnainen ja usein hienovarainen. Paikalliset brändit eivät toimi suorina integraation indikaattoreina, vaan niiden merkitys rakentuu arjen käytäntöjen, sosiaalisen tunnistettavuuden sekä suomalaisuuteen liittyvien laajempien kulttuuristen merkitysten kautta.
Keywords: brands; identity (mental objects); acculturation; Finnish identity; consumption; consumer behaviour; Finland; Finns; marketing; consumer culture; fi=Markkinointi|en=Marketing|; fi=Markkinoinnin johtamisen maisteriohjelma|en=Master's Programme in Marketing Management|